Fallout : Conspiracy, Cover-Up, and the Deceitful Case for the Atom Bomb - Watson, Peter, 1943- (London : Simon & Schuster, 2018)
"The justification for the atomic bomb was simple: it would defeat Hitler and end the Second World War faster, saving lives. The reality was different. [This book] dismantles the conventional story of why the atom bomb was built. Peter Watson has found new documents showing that long before the Allied bomb was operational, it was clear that Germany had no atomic weapons of its own and was not likely to. The British knew this, but didn't share their knowledge with the Americans, who in turn deceived the British about the extent to which the Soviets had penetrated their plans to build and deploy the bomb. The dark secret was that the bomb was dropped not to decisively end the war in the Pacific but to warn off Stalin's Russia, still in principle a military ally of the US and Britain. It did not bring a hot war to an abrupt end; instead it set up the terms for a Cold one to begin. Moreover, none of the scientists recruited to build the bomb had any idea that the purpose of the bomb had been secretly changed and that Russian deterrence was its new objective. Fallout vividly reveals the story of the unnecessary building of the atomic bomb, the most destructive weapon in the world, and the long-term consequences that are still playing out to this day."--Jacket.
Preface--Cover-up: 'When the righteous sin' -- PART ONE: Incognito: Klaus Fuchs and Niels Bohr. Zigzag -- PART TWO: The overestimate of the Germans. The taste of fear : the menace of fission ; The beginnings of a 'strategic game' ; Struggles over secrecy ; The midwives ; The strategic sabotage of heavy water ; The first glimpses of Germany's nuclear secrets ; The 'crown jewel' of secrets ; Intelligence blackout : the fatal mistake ; Fall out ; 'Hard evidence' of Soviet spying ; The secret agenda of General Groves ; The Bohr scare ; A vital clue vanishes ; 'Don't bother me with your scruples' : the loss of innocence ; The claws of the bear -- PART THREE: Lives in parallel: Niels Bohr and Klaus Fuchs ; The little fox ; Lunch in the Supreme Court ; 'The mission he had been waiting for' ; A president 'eager for help' ; The letter from Moscow ; The Prime Minister's mistake ; The bomb in trouble : mistakes at Los Alamos ; The President's mistake -- PART FOUR: The underestimate of the Russians. Bohr and Stalin ; Fuchs : shining in the shadows.
"A new history."
Includes bibliographical references (pages 371-398) and index.
Keywords: 1939-1991; World War, 1939-1945 -- Diplomatic history; Atomic bomb -- Political aspects; Atomic bomb -- United States -- History; Atomic bomb -- Soviet Union -- History; Nuclear arms control; Cold War; HISTORY -- Military -- Nuclear Warfare; HISTORY -- Military -- World War II; SCIENCE -- Physics -- Nuclear; Atomic bomb; Atomic bomb -- Political aspects; Diplomatic history; Diplomatic relations; Nuclear arms control; United States -- Foreign relations -- Soviet Union; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- 1945-1953.; Soviet Union -- Foreign relations -- 1945-1991.; Soviet Union; United States; History